“Being then nothing”: Physicality, abjection and creation in Janice Galloway’s short fiction - Sacido Romero, Jorge (International Journal of English Studies, 2019)
This article explores the prominence of the body in Janice Galloway’s short fiction. Drawing mainly on Kristeva’s notions of the semiotic and the abject, the argument initially establishes the central place of physicality in Galloway’s poetics. Her creative project is inspired by a desire to transmit in writing the experience of being alive, of how being is intrinsically fragile, inexorably bound to extinction. In a particularly sharp manner that engages the reader more actively than her novels, her short stories exhibit both formally and thematically an interaction of the symbolic and the semiotic. As being attentive to life entails an awareness of death if one is to write realistically, the ensuing discussion of stories from her three collections –Blood (1991), Where you find it (1996) and Jellyfish (2015)– reveals that abjection, the extreme version of the semiotic that threatens to cancel out the symbolic, is paramount in her creative universe.